Diversity and composition of gut protist in young rural Zimbabwean children - Pfavayi, Lorraine Tsitsi; Sibanda, Elopy Nimele; Baker, Stephen; Woolhouse, Mark; Mduluza, Takafira; Mutapi, Francisca (Frontiers in Microbiomes, 2024)
Background: The human gut microbiome harbours diverse species of archaea, bacteria, fungi, protists and viruses. To date, most gut microbiome studies have focused on bacteria, neglecting other microbial communities. Consequently, less is known about the diversity and abundance of the latter. Here, we aimed to characterise the diversity and composition of protists in the gut of preschool-aged children (PSAC) in rural Zimbabwe relative to host age, sex, and schistosome infection status.The gut protist of 113 PSAC (1-5 years) was examined via shotgun metagenomic sequencing and analysed for diversity. Variation in protist abundance with host and environmental factors was analysed by permutational multivariate analysis of variance (PERMANOVA). To investigate how the composition of specific taxa varies across age, sex, nutritional measures and Schistosoma hematobium infection status, analysis of the composition of microbiomes (ANCOM) was used.Results: Eighty protist genera were identified, and the most abundant genera detected was Blastocystis. The prevalence of pathogenic protists was comparatively low, with 12.4% and 3.4% of the participants' gut colonised by E. histolytica and Cryptosporidium, respectively. Of all the independent variables only S. haematobium infection showed significant relationship with the structure of the gut protist, being associated with increases in Peronospora, Pseudoperonospora, Plasmopara and Blastocystis (FDR= 0.009).